Epidemiologic study of Blastocystis infection in Pateros, Metro Manila - Belleza, Maria Luz B.
Blastocystis is a prevalent gastrointestinal protozoan infecting humans and different animals. Differences in the magnitude of infection have been reported worldwide. The genetic diversity of Blastocystis has also been observed, with 10 different subtypes (subtypes 1,2,3,4,5,6,7,8,9,10) identified from different hosts. Blastocystis is transmitted in different studies. This cross-sectional study determined the prevalence of Blastocystis infection in a community, and estimated its magnitude of association with correlates such as sociodemographic factors, hygiene practices: hand washing and excreta disposal, source of water supply and dog ownership. Blastocystis subtypes from human and dog isolates were also identified, and concordance between the infection status and each Blastocystis subtype was determined. The study was conducted in 1271 individuals who responded in the interview and submitted stool samples. All stool samples including those from dogs of identified dog owners were cultured in a diphasic agar medium for 3-5 days. To identify Blastocystis subtypes, DNA samples were extracted from the isolates, and examined by polymerase chain reaction using 7 subtype specific primers of Blastocystis. The prevalence of Blastocystis infection in this study was 13%. Among the correlates examined, age, level of education (high school OR=1.8, 90% CI: 1.2-2.6 and no education OR=3.1, 90% CI: 1.7-5.3) and dog ownership (OR 2.6, 90% CI: 1.9-3.7) were found significantly associated with the infection. Blastocystis subtypes 1,3, 5,6 and 7 were identified from both human and dog isolates. Concordance between Blstocystis infection in humans and dogs showed a fair agreement (K= 0.358), while concordance between Blastocystis subtypes revealed a slight agreement for subtypes 3 (K=0.40), a fair agreement for subtype 6 (K=0.317) and a less than chance agreement for subtype 1, 5 and 7 (K= -0.014, K= -0.011, and K= -0.0248). The study showed that Blastocystis is prevalent in the community. The correlates of Blastocystis infection such as age, level of education and dog ownership contributed to the understanding of the role of these factors in acquiring the infection. Therefore, these factors should be considered in the development of information, education and communication messages to create awareness about Blastocystis, and to prevent and control Blastocystis infection in particular and diarrheal diseases in general. In addition, the isolation of subtypes 1 and 7, which previous reports have been cited as having higher level of pathogenecity indicated the risk of symptomatic infection, while identification of the same subtypes from dog owners and their pet dogs although not conclusive of cross transmission, could mean cross infectivity. Further analysis on the DNA samples from humans and dogs can be used to further analyze their genetic relationship, and provide more conclusive evidence of the presence of cross transmission between them. While increase in sample size of dogs and dog owners is recommended to generate a more definite analysis of the concordance in the infection status and Blastocystis subtypes that are present.
Thesis (MS Public Health, Parasitology)--University of the Philippines Manila, 2013
Keywords: Blastocystis infection